(untitled) (Proceedings of the International Conference on Future of Education, 2025)
This study investigated leadership styles among administrators in an academic institution to develop a training plan for future administrators. The research aimed to identify prevalent leadership styles, assess differences in perception between administrators and staff, determine the use of agile leadership, and explore the relationship between leadership style and responsiveness in various situations. A mixed-methods approach was employed, using a researcher-designed survey administered to 105 employees (52 administrators and 53 staff) and key informant interviews with three administrators. Quantitative data was analyzed using descriptive statistics (frequency, weighted mean) and inferential statistics (Pearson correlation, z-test). Qualitative data from interviews provided context and validation. Results indicated a perceived discrepancy in leadership styles, with staff primarily experiencing transactional leadership and administrators believing they employed transformational leadership. Responsiveness levels were generally high across situations, with specific leadership skills emerging depending on the context. The study identified servant leadership as effective in normal situations, transformational leadership in emergencies, and agile leadership in conflict resolution. Based on these findings and identified challenges and solutions, a proposed training plan was developed. The study concludes that situational leadership is crucial, emphasizing the need for tailored approaches. It suggests that faculty can play a key role in developing future leaders by incorporating leadership training and practical application into their curriculum.